(untitled) (Research, Society and Development, 2022)
This study sought, from an integrative literature review, to observe which biosecurity measures are being taken by the dental class to control infection after the emergence of the Covid-19 pandemic. The search for articles was carried out between November 2021 and May 2022, in the bibliographic databases SCIELO (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature in Health Sciences) and PUBMED (National Library of Medicine National Institutes of Health of the USA) through the descriptors biosafety, Covid-19, coronavirus and dentistry. From a total of 76 articles found with these descriptors, 37 articles were excluded after reading the title and abstract and 34 after reading the full text, and 5 studies were selected for this review. It was possible to observe that in all areas of dental care, even in educational institutions, the importance of maintaining biosafety procedures was reassessed, with the progressive resumption of face-to-face consultations, so that it figured as a watchword in all highlighted scenarios. It is concluded, emphasizing that the studies demonstrate that there was a concern for the prevention of Covid-19, in which biosecurity represents the main means to guarantee the health of patients and professionals.